Generalized definition of "crack-like" notches to finite life and SN curve transition from "crack-like" to "blunt notch" behavior. (15th June 2017) - Ciavarella, M.; D'Antuono, P.; Demelio, G.P.
Highlights: We generalize the concept of "crack-like" notches to finite life, according to Critical Distance Method. SN curves of all notches are very close to SN curves for cracked specimen, up to a certain number of cycles N ∗ . Above N ∗, they tend to the SN curve of the uncracked/unnotched (plain) specimen, reduced by Kt. New simple estimates for SN curves of notches are suggested. The comparison with known SAE keyhole tests leads to better agreement with experiment than strain-life approaches. Abstract: We start by generalizing the concept of "crack-like" notches to finite life. We note that, according to the well established Critical Distance Method (originally proposed by Neuber and Peterson), SN curves of all notches are very close to SN curves for cracked specimen, up to a certain number of cycles N ∗, above which they tend to the SN curve of the uncracked/unnotched (plain) specimen, reduced by the stress concentration factor K t . We suggest therefore new simple estimates for rapid assessment of the notch effect under finite life: for the "crack-like" notch, substituting the notch with a crack leads to immediate use of crack solutions in databases, whereas the knowledge of the stress ahead of a notch is also well known analytically in many cases, or can be adapted. We show one example with the SAE keyhole tests, leading to fully analytical SN curves, in much better agreement with experiment than, for example, strain-life approaches using Neuber's rule.